An Alternative Modular Wooden System for Fast Assembly/Disassembly of Buildings - Marco Bovo; Enrica Santolini; Alberto Barbaresi (Buildings)
Throughout human settlement history, the pursuit of durability has been a paramount objective in building construction. The emphasis on durability has resulted in the construction of buildings designed to outlast human lifespans. However, the lack of consideration for building demolition and disposal during the design and construction phases has created challenges for future generations. This oversight contributes to the environmental impact of structures after demolition, which is a significant concern given that the construction industry is a major contributor to energy consumption, CO2 emissions, and solid waste production. In fact, in recent decades, there has been an increasing demand for temporary constructions, driven by factors such as migration phenomena, natural disasters, and the COVID-19 pandemic, but also in sectors like agriculture, where seasonality and annual variations in activities require adaptable structures such as warehouses, barns, livestock shelters, and food storage facilities. Unlike traditional constructions, these temporary buildings must be assembled and disassembled multiple times during their lifespan. The challenge lies in ensuring the structural integrity, adaptability to varying conditions, and compliance with specific requirements to extend their usability and postpone the disposal phase. This study focuses on the design of a novel type of temporary structures intended for temporary needs such as emergencies and planned agricultural activities, resulting in a European patent. The structure is based on a glulam frame inside two OSB panels—that work as structural bracing, creating a hollow, resistant, light structure—connected with external steel connections. This work reports results of mechanical simulations and thermal transmittance calculations. Specifically, it demonstrates the building maintains structural strength through multiple usages and its thermal characteristics can be easily adapted to the context. These are the first steps for a resilient and sustainable building.